Choice of Counsel and the Appearance of Equal Justice Under Law - Wesley M. Oliver (2014)
Once a federal prosecutor obtains an indictment that seeks a forfeiture, a judge must permit the prosecutor to freeze all the potentially forfeitable assets that would be unavailable at the time of conviction. Obviously, funds used for the defense would fit into that category. Equally obvious is the tension between the government’s interest in assets that may be forfeitable and a defendant’s Sixth Amendment right to choice of counsel. A number of lower courts therefore had permitted defendants to seek release of the assets needed for a defense by challenging the grand jury’s determination that probable cause existed to believe crimes subjecting the assets to forfeiture have been committed. Denying such a hearing permits the prosecution to decide both that a defendant should face trial and should do so without his counsel of choice. In an opinion that therefore seems somewhat shocking, the Supreme Court in Kaley v. United States rejected the defendants’ claim that they had a Sixth Amendment right to such a hearing. A different decision, however, would have required lower courts to determine what amount of potentially forfeitable assets could be released to fund a defense. Either courts would have released the amount of money that would be provided for an indigent, thus still effectively denying the right to counsel of choice, or courts would have identified a greater amount of money needed for a private defense, highlighting the justice gap between rich and poor